The Central Role and Possible Mechanisms of Bacterial DNAs in Sepsis Development - Zhenxing Cheng; Simon T. Abrams; James Austin; Julien Toh; Susan Siyu Wang; Zhi Wang; Qian Yu; Weiping Yu; Cheng Hock Toh; Guozheng Wang (Mediators of Inflammation)
The pathological roles of bacterial DNA have been documented many decades ago. Bacterial DNAs are different from mammalian DNAs; the latter are heavily methylated. Mammalian cells have sensors such as TLR-9 to sense the DNAs with nonmethylated CpGs and distinguish them from host DNAs with methylated CpGs. Further investigation has identified many other types of DNA sensors distributed in a variety of cellular compartments. These sensors not only sense foreign DNAs, including bacterial and viral DNAs, but also sense damaged DNAs from the host cells. The major downstream signalling pathways includeTLR-9-MyD88-IKKa-IRF-7/NF-κB pathways to increase IFN/proinflammatory cytokine production, STING-TBK1-IRF3 pathway to increase IFN-beta, and AIM2-ASC-caspas-1 pathway to release IL-1beta. The major outcome is to activate host immune response by inducing cytokine production. In this review, we focus on the roles and potential mechanisms of DNA sensors and downstream pathways in sepsis. Although bacterial DNAs play important roles in sepsis development, bacterial DNAs alone are unable to cause severe disease nor lead to death. Priming animals with bacterial DNAs facilitate other pathological factors, such as LPS and other virulent factors, to induce severe disease and lethality. We also discuss compartmental distribution of DNA sensors and pathological significance as well as the transport of extracellular DNAs into cells. Understanding the roles of DNA sensors and signal pathways will pave the way for novel therapeutic strategies in many diseases, particularly in sepsis.